The analysis of ALK gene rearrangement by fluorescence in situ hybridisation in non-small cel lung cancer patients - Wojas-Krawczyk, Kamila; Krawczyk, Paweł Adam; Ramlau, Rodryg Adam; Szumiło, Justyna; Kozielski, Jerzy; Kalinka-Warzocha, Ewa; Bryl, Maciej; Knopik-Dąbrowicz, Alina; Spychalski, Łukasz; Szczęsna, Aleksandra; Rydzik, Ewelina; Milanowski, Janusz (Contemporary Oncology/Współczesna Onkologia, 2013)
Introduction : ALK gene rearrangement is observed in a small subset (3–7%) of non-small cell lung cancer (NSCLC) patients. The efficacy of crizotinib was shown in lung cancer patients harbouring ALK rearrangement. Nowadays, the analysis of ALK gene rearrangement is added to molecular examination of predictive factors. Aim of the study: The frequency of ALK gene rearrangement as well as the type of its irregularity was analysed by fluorescence in situ hybridisation (FISH) in tissue samples from NSCLC patients. Material and methods: The ALK gene rearrangement was analysed in 71 samples including 53 histological and 18 cytological samples. The analysis could be performed in 56 cases (78.87%), significantly more frequently in histological than in cytological materials. The encountered problem with ALK rearrangement diagnosis resulted from the scarcity of tumour cells in cytological samples, high background fluorescence noises and fragmentation of cell nuclei. Results: The normal ALK copy number without gene rearrangement was observed in 26 (36.62%) patients ALK gene polysomy without gene rearrangement was observed in 25 (35.21%) samples while in 3 (4.23%) samples ALK gene amplification was found. ALK gene rearrangement was observed in 2 (2.82%) samples from males, while in the first case the rearrangement coexisted with ALK amplification. In the second case, signet-ring tumour cells were found during histopathological examination and this patient was successfully treated with crizotinib with partial remission lasting 16 months. Conclusions: FISH is a useful technique for ALK gene rearrangement analysis which allows us to specify the type of gene irregularities. ALK gene examination could be performed in histological as well as cytological (cellblocks) samples, but obtaining a reliable result in cytological samples depends on the cellularity of examined materials.